2021
DOI: 10.3390/w13202859
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase-5 (PDE-5) Inhibitors as Emergent Environmental Contaminants: Advanced Remediation and Analytical Methods

Abstract: Pharmaceuticals, fundamental in therapy and the prevention of known pathologies, are responsible for environmental pollution. These substances, called “emerging contaminants,” are harmful to human health because they enter the environment in quantities exceeding the natural self-capacity purification of the ecosystems. Furthermore, wastewater treatment plants (WWTPs) cannot remove these substances, which can undergo chemical/biological transformations in the environment, thus forming by-products, sometimes mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…The dosage of tadalafil employed in our study was chosen based on previous research 21 . However, a study by Bianco et al [ 21 ] indicated that there is no human health risk for exposure to sildenafil (LC50 = 42.74 for B. calyciflorus ) and tadalafil (LC50 = no effect up to 20 for B. calyciflorus ). However, they require special care as this form of contamination is found in any aquatic system evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The dosage of tadalafil employed in our study was chosen based on previous research 21 . However, a study by Bianco et al [ 21 ] indicated that there is no human health risk for exposure to sildenafil (LC50 = 42.74 for B. calyciflorus ) and tadalafil (LC50 = no effect up to 20 for B. calyciflorus ). However, they require special care as this form of contamination is found in any aquatic system evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…One hundred and twenty fish ( O. niloticus) were selected and divided into four treatments, each treatment contains 30 fish in triplicates (as 10 fish for each) in 96L glass aquarium water. The fish were distributed into 1st group control group (fish exposed to only water); 2nd group exposed to 10 mg/LPE-MPs 15 ; 3rd group exposed to 20 mg/l tadalafil (Cilais) 21 ; 4th group exposed to 20 mg/l tadalafil (Cilais) + 10 mg/LPE-MPs. Twelve fish from each group were chosen at random after 15 days of exposure and put unconscious with crushed ice 36 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have shown that ED results from cardiovascular diseases and other health problems, such as smoking, high blood pressure, high cholesterol, metabolic syndrome, and diabetes. However, it can also be caused by (i) neurological (deficit in nerve signaling to the "corpora cavernosa"), (ii) psychological (depression, stress, or anxiety), or (iii) endocrinologic (low testosterone levels or other hormone imbalances) factors [6][7][8][9]. Several PDE5Is are currently on the market, including the FDA-approved medications sildenafil, vardenafil, tadalafil, and avanafil, as well as the non-FDA-approved medications lodenafil, udenafil, and mirodenafil [10].…”
Section: Introductionmentioning
confidence: 99%